O telejornal local "a serviço" do cidadão: um estudo do Jornal Anhanguera 1ª edição - Rocha, Jordânia Bispo (2018)
This research discusses journalism and citizenship with an emphasis on local television journalism. The general objective is to know how the subject citizenship was approached in the content of the local telejornalismo in the period of 2010 to 2017. To reach the expected results, this study uses as an object of analysis the Jornal Anhanguera 1a edition, television news program shown at lunchtime by TV Anhanguera, an affiliate of Rede Globo de Televisão in Goiás. This decision is due to the fact that the news in question underwent an intense process of changes in 2010 and since then, it has privileged issues related to citizenship in its content. The analysis is guided by the theoretical framework, which is divided into four chapters. The first begins the articulation of the central themes, emphasizing the concepts of communication (SODRÉ, 2001, 2008, 2014; MARCONDES FILHO, 2008; BRAGA, 2001) and citizenship (PINSKY e PISNSKY, 2005; CARVALHO, 2014; SANTOS, 1994; BENEVIDES, 1994; GENTILLI, 2005; SOUZA, 2012), and presenting the Brazilian scenario. The second discusses journalism, its different facets and its process of structural changes (KOVACH e ROSENSTIEL, 2004; CHARRON e DE BONVILLE, 2016; GROTH, 2011; TRAQUINA, 2005; MARCONDES FILHO, 2002, GENRO FILHO, 1987). While the third deals with television journalism and local television journalism in its specificity (STAM, 1985; REZENDE, 2000; VIZEU, 2005; PORCELLO, 2006; MORAES, 2012; AGUIAR, 2016), including the recent transformations that both have experienced (BECKER, 2016; SOUZA FILHO, 2015). Finally, the last theoretical chapter deals strictly with the relationship between journalism and citizenship, highlighting the advantages of journalism as an ally in the construction of citizenship (ABREU, 2009; GENTILLI, 2005; GRADIM,2015). The analysis is conducted mainly from the Content Analysis proposed by Bardin (2010) and is divided into three moments: systematic observation of eight complete editions of the journal in question, as well as 38 specific journalistic articles on citizenship and the "Meus Direitos" since its inception. The research showed, among other points, that the approach to issues related to citizenship is a television news strategy to strengthen ties with a new target audience and that this term in itself, citizenship, is not used by Jornal Anhanguera 1a edição, but serves as a starting point for a significant part of the journalistic agenda today. The distinction of citizen profiles in the analyzed content was also evident, just as it was found that new Information and Communication Technologies have played equally strategic roles from the beginning of the process of reformulating the broadcaster in 2010 until the end of 2017.